Prevalence of depression in patients with end-stage renal disease undergoing hemodialysis in Saudi Arabia: A cross-sectional study - Lujain Sallam; Fatmah Alsharif; Sarah Abaalalaa; Rawan Alakeely; Zahraa Abdullah; Zahra Alkhamis; Najla Sindi; Loujain S Sharif (Belitung Nursing Journal, 2022)
Background: A hemodialysis is a treatment option for patients with End-Stage Renal Disease (ESRD). However, patients undergoing hemodialysis three times per week may experience psychological issues, including depression, which are highly prevalent among patients. Unfortunately, most healthcare providers fail to recognize the symptoms of depression due to overlap with other somatic symptoms; thus, depression remains undiagnosed. Objective: This study aimed to estimate the prevalence of depression and compare the differences in depression symptoms according to the sociodemographic characteristics of patients with ESRD undergoing hemodialysis. Method: A descriptive, cross-sectional study was conducted from August to October 2021 with a total of 132 hemodialysis patients using the Beck Depression Inventory (BDI II) questionnaire to examine symptoms of depression at multiple health centers in Jeddah. Descriptive statistics, Mann-Whitney U, Kruskal-Wallis, Post-hoc analysis using Conover tests were used for data analysis. Results: The prevalence of depression in hemodialysis patients was 51.5%, 25.8%, 15.9%, and 6.8%, with minimal, mild, moderate, and severe symptoms, respectively. Depression exhibited a significant relationship with sex (p = 0.034), with females showing higher mean depression scores than males. Additionally, depression scores were statistically significant across the different levels of education (p = 0.019), with the mean depression scores significantly highest in subjects who had only primary school level of education. Furthermore, the most common symptoms associated with depression were found to be energy loss and fatigue. Conclusion: Depression prevalence was relatively low among patients with ESRD undergoing hemodialysis, and a loss of energy and fatigue were the most common symptoms correlated with depression. Hence, nurses should be trained on how to routinely use psychological screening scales among patients with ESRD undergoing hemodialysis.